High-altitude cerebral hypoxia promotes mitochondrial dysfunction and apoptosis of mouse neurons - Huan, Yu; Quan, Huilin; Jia, Bo; Hao, Guangzhi; Shi, Zuolin; Zhao, Tianzi; Yuan, Ying; Yuan, Fang; Dong, Yushu; Liang, Guobiao (Frontiers in Molecular Neuroscience, 2023)
Acute high altitude leads to neuronal cell death, however, the cellular and molecular mechanisms of this pathological process is less clear. In this study, we first tested if high-altitude hypoxia (HAH) causes neuronal death and mitochondrial dysfunction using various in vivo and in vitro approaches. We observed that HAH disrupted mitochondrial function and promoted neuronal apoptosis and necroptosis both in HT-22 cells and in mouse hippocampal neurons. Moreover, the mitochondrial membrane potential and adenosine triphosphate production decreased in neurons after HAH, while oxidative stress and mitochondrial fission increased. Behavioral studies suggested that HAH induced anxiety-like behavior and impaired spatial memory, while it had no effect on athletic ability. These findings demonstrated that HAH promotes mitochondrial dysfunction and apoptosis of mouse neurons, thus providing new insights into the role of mitochondrial function and neuronal cell death in acute high-altitude cerebral hypoxia.